Media Literacy and the Reception of Negative News Among Generation Z: Findings from Banda Aceh - Susilawati, Novi; Halfiani, Vera; Wahyuni, Putri (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2024)
The increasing prevalence of negative news in digital media has raised concerns about its psychological impacts, particularly on Generation Z (Gen Z), who are deeply immersed in digital technology. Media literacy is believed to play a crucial role in mitigating these impacts by enabling individuals to critically evaluate information. This study explores the influence of media literacy on the reception of negative news among Gen Z in Banda Aceh. Using a quantitative approach, data were collected from 281 respondents aged 1826 years through an online questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships between exposure to negative news, digital literacy, and information reception. The findings reveal that neither exposure to negative news nor the level of digital literacy significantly affects how Gen Z processes and interprets negative information. Despite the non-significant relationships, the study emphasizes the role of media literacy as a vital skill for Gen Z in critically filtering and assessing digital content. The study highlights the necessity of enhancing media literacy to foster resilience against the psychological risks posed by negative news in the digital ecosystem. By equipping Gen Z with critical thinking skills and digital competencies, individuals can better navigate the overwhelming flow of information in online media. Future research should further investigate the long-term effects of media literacy on psychological well-being and behavioral outcomes.